Prinsip Perancangan Sebagai Dasar Penanganan Konflik Padda Koridor Jalan Komersial (Kasus Studi: Koridor Jalan Komersial Kota Bandung) - Petrus Natalivan (Journal of Regional and City Planning, 2003)
The use of commercial corridors as public space raises varying conflicts, coming from physical, functional and behavioral problems. The conflicts should be treated to eliminate/reduce social unrest, and looses to stakeholders and commercial activities. This research is aimed at formulating design principles for orderly and fairly commercial corridors as public space. The formulation of these principles is carried out through demand side which relates to right and interest of stakeholders and supply side which relates to structural and functional characteristic of commercial corridors.Keywords: public space, commercial corridor, design principles, conflicts management, conflicts resolution